Architecture of automated control and accounting objects energy sphere of education - Захарченко, Ю. А.; Соколова, Н. П.; Вітер, В. В. (Problems of Informatization and Control, 2015)
An architecture of hardware and software that enables the integration of information flows locallymeasuring units in common measuring-information space for simultaneous, continuous, automaticgeneration of process control, transportation and energy consumption targets education